Farm production, marketing, and children's nutritional outcomes in rural Zambia - Mulungu, Kelvin; Manning, Dale T.; Kumwenda, Chiza; Mwelwa, Lukonde; Mudenda, Lackson Daniel (Wiley Periodicals LLC, 2025)
Despite increasing agricultural productivity, malnutrition remains high among food producers in many developing countries. This study examines how the difference between agricultural household nutrition requirements and production kept for home consumption, the Nutritient deficiency from own production (NDOP), impacts children's height-for-age z-scores (HAZ) using a unique survey of 528 households in Zambia. The study also investigates the relationship between NDOP and market-bought nutrition and the role of intra-season price changes in nutrition. To address the endogeneity of NDOP, we use a control function approach. We find that NDOP is associated with lower HAZ. Both energy (calories) NDOP and nutrient-specific NDOP, resulting from underproduction relative to nutritional requirements and from selling more than surplus food crops, are negatively correlated with HAZ. This result suggests that higher productivity and market participation do not always lead to better nutrition. We also find that crop sales (commercialization) only benefit nutrition if the household only sells surplus output relative to its nutritional requirements. Finally, we also find that NDOP does not correlate with market food purchases, and that the seasonal price increases for cereals further dampens market food purchases. The findings highlight that policies promoting smallholder commercialisation may overlook detrimental nutrition trade-offs when own-production falls short of household needs. Accounting for post-harvest allocation of nutrients between own-consumption, sales, and purchases can help ensure agricultural interventions improve farmer livelihoods and child nutrition.